(untitled) (Caligrama: Revista de Estudos Românicos, 2020)
Abstract: This study addresses Lope de Aguirre’s Letter to the King as one of the innumerous materials that relates to the aesthetics of hunger in Glauber Rocha’s work. The writing of the letter itself is a document of resistance through Andean as well as Amazonian territories: against institutional power, religious values, justice, and corruption. In doing so, the letter shares the main characteristics present in the works of art produced by Glauber Rocha during Cinema Novo. This means that the aesthetics of hunger should be understood as an atemporal response to historical and structural violence, instead of an aesthetical phenomenon limited to the context of Cinema Novo in Brazil. In more practical terms, this investigation identifies the mechanisms of the aesthetics of hunger in Lope de Aguirre’s Letter to the King. It demonstrates that such aesthetics is a collective recurrent phenomenon in Latin America’s history since its colonization. The aesthetics of hunger, thus, contests not only the work of art in the 20th century through Cinema Novo, or the tradition of foundational documents (travel chronicles) in the late 1400s and early 1500s, but most importantly, it allows literary criticism to approach the matter of hunger as a counterpoint to – not a form of subjugation by – (post)colonial practices. Keywords: hunger; Andean; Amazonian; violence; Latin America. Resumo: Este estudo aborda a Carta de Lope de Aguirre ao Rei como um dos inúmeros materiais que dialogam com a estética da fome na obra de Glauber Rocha. A redação da carta em si mesma é um documento de resistência nos territórios andinos e amazônicos: contra o poder institucional, valores religiosos, justiça e corrupção. Portanto, a carta compartilha as principais características presentes nas obras de arte produzidas por Glauber Rocha durante o Cinema Novo. O que isto significa é que a estética da fome deve ser entendida como uma resposta atemporal à violência histórica e estrutural, em vez de um fenômeno estético limitado ao contexto do Cinema Novo no Brasil. Em termos mais práticos, esta investigação identificará os mecanismos da estética da fome na Carta de Lope de Aguirre ao Rei. A análise em questão demonstra que tal estética é um fenômeno recorrente e coletivo na história da América Latina desde sua colonização. A estética da fome, portanto, contesta não apenas a obra de arte do século XX através do Cinema Novo, ou a tradição de documentos fundacionais (crônicas de viagem) no final de 1400 e início de 1500, mas permite, para além disso, que a crítica literária aborde a questão da fome como um contraponto a – não uma forma de subjugação por – práticas (pós)coloniais. Palavras-chave: fome; andinos; amazônicos; violência; América Latina.